Interregional migration of employees in the EU with particular attention paid to Poland in the process of deepening the European economic integration - Dziembała, Małgorzata (Publishing House of the Wrocław University of Economics, 2009)
The aim of the article is to depict a situation in regional labour markets in the EU member states in the context of progressing process of deepening economic integration and to compare the phenomenon of spatial mobility of employees, taking into account interregional migrations occurring in Poland. The size of means of the European cohesion policy are presented. They are directed to particular areas of intervention in the years 2007-2013, which are to improve the difficult situation in the labour markets in problematic areas as well. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 132-143